The Placement of Four Short Implants and Full-Arch Early Loading in the Edentulous Patient Suffering from Severe Mandibular Alveolar Ridge Atrophy - Yuri Sedov; Oleg Mordanov; Sergei Grigoriev; Anatoly Avanesov; Kamil Khabiev (Case Reports in Dentistry)
One of the treatments of patients with severe bone atrophy is short implants. It is important to position short implants taking into account the prosthetic loading and right position according to vital anatomical structures. In the presented case report, a seventy-one-year-old female patient underwent the rehabilitation with four short dental implants placed in the anterior mandibula with fully guided surgery to avoid mandibular incisive canal. It solves all the problems in the planning stage when you determine the osteotomy protocol in advance and the prognosis of future restoration according to patient requirements. This clinical case demonstrates the efficiency of patient rehabilitation with the use of short implants in difficult clinical situations.